Tendência temporal das hospitalizações por bronquiolite aguda em lactentes menores de 1 ano no Brasil, 2008-2015 - Tumba, Kanama (2017)
Introduction: acute bronchiolitis is one of the most common respiratory diseases of early childhood. It is the main cause for hospitalization of children in developed countries during winter time. Currently, despite advances in medicine, there is still no evidence of specific and effective treatment for acute bronchiolitis. In order to prevent the disease, the Brazilian Ministry of Health, in July 2013, has made palivizumab available to high-risk children throughout Brazil. Objective: to assess the trend of hospitalization for acute bronchiolitis in infants under 1 year of age, before and after the implementation of the palivizumab immunization program in Brazil. Methods: retrospective analysis of data from infants under 1 year of age hospitalized with a diagnosis of acute bronchiolitis between 2008 and 2015 in Brazil, using a database of the Brazilian National Health System. The incidence of pre-implementation (2008-2012) and post-implementation (2014-2015) admissions was analyzed. Results: between January 2008 and December 2015, 263,654 hospitalizations for bronchiolitis were registered in infants under 1 year of age, 60% represented by boys. The incidence of hospitalization for bronchiolitis increased 49,4% during this period (from 8.5 to 12.7 per 1000 inhabitants per year), with an annual incidence rate of 10.9 per 1000 inhabitants per year. Between 2013 and 2014, the incidence rate of hospitalization for acute bronchiolitis decreased 8% (from 12.5 to 11.5 per 1000 inhabitants per year). In the second year of the program, the hospitalization rate increased 10% again (from 11.5 to 12.7 per 1000 inhabitants’ year). Conclusion: the incidence of acute bronchiolitis showed an increasing trend. Hospitalizations declined one year after implementation of palivizumab and returned to increasing trend in the second year of the program.